Amygdalin improves microcirculatory disturbance and attenuates pancreatic fibrosis by regulating the expression of endothelin‐1 and calcitonin gene‐related peptide in rats. Issue 5 (May 2018) - Zhang, Xiangqun; Hu, Jiangong; Zhuo, Yuzhen; Cui, Lihua; Li, Caixia; Cui, Naiqiang; Zhang, Shukun
Abstract : Background: : The pathogenesis of chronic pancreatitis (CP) is a complex process of interaction between tissue injury and repair, which involves microcirculatory disturbance. Amygdalin, an effective component extracted from Semen Persicae (a kind of Chinese herbal medicine), can decrease blood viscosity and improve microcirculation. In this study, we investigated the therapeutic effects of amygdalin on pancreatic fibrosis in rats with CP. Methods: : The rat CP model was induced by injecting dibutyltin dichloride (DBTC) into the right caudal vein. Amygdalin was administrated via the penile vein at a dose of 10 mg/(kg d) from the next day, after the induction of CP, once a day for the previous 3 days, and then once every 2 days, until the end of the experiment. Body weight was observed every 7 days. Pancreatic blood flow and histopathological changes were assessed at 28 days. The activation of pancreatic stellate cells (PSCs) was estimated by the expression of α‐smooth muscle actin (α‐SMA). At the same time, the expression of platelet‐derived growth factor‐BB (PDGF‐BB), transforming growth factor β‐1 (TGFβ‐1), endothelin‐1 (ET‐1), and calcitonin gene‐related peptide (CGRP) of pancreatic tissues were detected. Results: : Treatment of CP rats with amygdalin improved body weight and pancreatic blood flow, as well as alleviated pancreatic fibrosis and acinar destruction, accompanied by the down‐regulation of the expressions of α‐SMA, PDGF‐BB, TGFβ‐1, and ET‐1, and the up‐regulation of the CGRP's expression. Conclusion: : Amygdalin could reduce the production of pro‐fibrotic cytokines, inhibit the activation of PSCs, and attenuate pancreatic fibrosis in a rat with CP. The mechanism probably includes improving microcirculatory disturbance by regulating the production of ET‐1 and CGRP.